Ceramic diaphragm for separating waste lubricating oil and preparation method of ceramic diaphragm

By using silk protein nanofibers in ceramic diaphragm composited with hydroxyapatite and coating the treated diatomaceous earth on the surface, the problems of excessive flux, unstable and poor adaptability of traditional ceramic diaphragm films are solved, and a more efficient, stable and flexible separation effect of waste lubricant is achieved.

CN119701679AActive Publication Date: 2025-03-28ZHONGKE TIANHAI (BEIJING) TECH CO LTD

Patent Information

Application Number
CN202411909983.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

In the process of separation of waste lubricant, traditional ceramic diaphragms have problems such as excessive film flux, unstable and poor adaptability, resulting in poor separation effect, damaged equipment stability and high maintenance costs.

Method used

Silk protein nanofibers reacted with epoxychlorohydrin and composited with hydroxyapatite powder, and prepared ceramic substrates by ball milling, sintering, etc.; at the same time, diatomaceous earth was calcined and triethylamine treated with polyethylene glycol and γ-aminopropyltriethoxysilane, coated on the surface of the ceramic substrate, and closely bonded through impregnation, drying and curing.

Benefits of technology

The rationality, stability and adaptability of membrane flux are achieved, the stability and repeatability of the waste lubricant separation process are improved, the equipment maintenance cost is reduced, and the service life of the diaphragm is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005205403710000162
    Figure BDA0005205403710000162
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic diaphragms, and particularly discloses a ceramic diaphragm for separating waste lubricating oil and a preparation method of the ceramic diaphragm. The preparation method of the ceramic diaphragm for separating the waste lubricating oil comprises the following steps: preparing pretreated fibroin nanofibers; mixing the pretreated silk protein nanofiber and hydroxyapatite powder, stirring, adding water, gelatin and sodium hexametaphosphate, carrying out ball milling, pouring into a mold, freeze-drying, sintering, cooling, and polishing the surface to obtain a ceramic base material; the preparation method comprises the following steps: calcining diatomite, cooling, adding absolute ethyl alcohol and water, stirring, adding triethylamine, stirring in a constant-temperature water bath, filtering, washing and drying to obtain pretreated diatomite; and mixing water, gamma-aminopropyltriethoxysilane and polyethylene glycol, stirring, adding the pretreated diatomite, stirring, immersing the ceramic base material, drying, and curing to obtain the ceramic diaphragm for separating the waste lubricating oil. According to the ceramic diaphragm for separating the waste lubricating oil, the membrane flux can keep self-adaptive constant-speed stability in a reasonable interval.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic diaphragms, and in particular to a ceramic diaphragm for separating waste lubricating oil and a preparation method thereof. Background Art

[0002] In today's industrial field, the proper treatment and reuse of waste lubricating oil has become a key link in the process of sustainable development. Among them, ceramic diaphragms play an important role in the separation process of waste lubricating oil. However, traditional ceramic diaphragms have exposed many defects that are difficult to ignore in practical applications.

[0003] First, the membrane flux of traditional ceramic diaphragms is often too high and deviates from the reasonable range. In the actual operation of waste lubricating oil separation, too high a membrane flux is not beneficial, but will lead to a series of adverse consequences. On the one hand, too high a membrane flux makes it difficult to achieve the ideal effect of impurity retention. Various impurities contained in waste lubricating oil, such as metal particles, oxidation products, colloids, etc., cannot be effectively blocked on one side of the diaphragm due to the high membrane flux, resulting in low purity of the separated lubricating oil, which cannot meet the subsequent reuse or emission standards. On the other hand, too high a flux will also damage the microstructure of the ceramic diaphragm itself. The strong fluid impact force and the rapid passage of impurities will cause the pore structure of the diaphragm to deform or even rupture. In the long run, it not only reduces the service life of a single diaphragm, but also greatly threatens the stability of the entire separation system. Frequent fault repairs and component replacements have become the norm, increasing the company's operating costs and time costs.

[0004] Secondly, it is difficult for traditional ceramic diaphragms to achieve uniform and stable membrane flux. When the waste lubricating oil separation operation is ongoing, the membrane flux will show irregular and large fluctuations. This instability directly leads to the inability to stably and accurately control the separation process. For example, in an automated waste lubricating oil treatment production line, fluctuations in membrane flux will cause the separation efficiency to fluctuate, and it will not be able to operate stably according to the preset process parameters, thus affecting the collaborative operation of the entire production line, resulting in low production efficiency and uneven product quality, while also increasing energy waste and equipment loss.

[0005] Finally, the adaptability of the membrane flux of traditional ceramic diaphragms is extremely poor when facing waste lubricating oils with different impurity contents and types. Waste lubricating oils come from a wide range of sources, and their composition is complex and varied. There are significant differences in the impurity content and impurity type of waste lubricating oils from different batches or sources. However, due to the limitations of its structure and material properties, traditional ceramic diaphragms cannot automatically adjust the membrane flux according to these changes. When treating waste lubricating oils with high impurity content or special impurity types, the diaphragm will quickly become clogged or damaged due to the inability to withstand the pressure; conversely, when treating relatively "clean" waste lubricating oils, the membrane flux may not be improved, resulting in low processing efficiency. This means that in actual production, it is necessary to frequently adjust the processing process for different waste lubricating oils, or even replace the ceramic diaphragm, which greatly increases the complexity and cost of equipment maintenance, reduces the reliability and flexibility of the entire waste lubricating oil treatment system, and is difficult to adapt to the large-scale and diversified waste lubricating oil treatment needs of modern industry.

[0006] In summary, traditional ceramic diaphragms have significant deficiencies in the rationality, stability and adaptability of membrane flux. There is an urgent need for an innovative ceramic diaphragm for waste lubricating oil separation and a preparation method thereof to overcome the limitations of the existing technology and to be able to flexibly, stably and efficiently perform separation operations based on the actual situation of the waste lubricating oil, thereby promoting the further development and improvement of waste lubricating oil treatment technology. Summary of the invention

[0007] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a method for preparing a ceramic diaphragm for separating waste lubricating oil.

[0008] A method for preparing a ceramic diaphragm for separating waste lubricating oil comprises the following steps:

[0009] S1, dispersing silk protein nanofibers in water, stirring, adjusting the pH value of the system, adding epichlorohydrin, stirring in a constant temperature water bath, filtering, collecting precipitates, washing, and drying to obtain pretreated silk protein nanofibers;

[0010] S2, mixing the pretreated silk protein nanofibers and hydroxyapatite powder, stirring, adding water, gelatin, and sodium hexametaphosphate, ball milling, pouring into a mold, freeze drying, sintering, cooling, and polishing the surface to obtain a ceramic substrate;

[0011] S3, calcining the diatomaceous earth, cooling, adding anhydrous ethanol and water, stirring, adding triethylamine, stirring in a constant temperature water bath, filtering, washing, and drying to obtain pretreated diatomaceous earth;

[0012] S4, mixing water, γ-aminopropyltriethoxysilane and polyethylene glycol, stirring, adding pretreated diatomaceous earth, stirring, immersing the ceramic substrate, drying, and curing to obtain a ceramic diaphragm for separating waste lubricating oil.

[0013] Preferably, the weight ratio of silk protein nanofibers, epichlorohydrin, hydroxyapatite powder, gelatin, sodium hexametaphosphate, diatomaceous earth, anhydrous ethanol, triethylamine, γ-aminopropyltriethoxysilane, and polyethylene glycol is 3-5:1.2-1.6:50-55:2.5-3.5:0.3-0.5:8-10:40-50:1.5-3:0.3-0.5:2-4.

[0014] Preferably, in step S1, the silk protein nanofibers are dispersed in deionized water and then stirred, the stirring time is 20-30 min, and the stirring speed is 250-350 rpm.

[0015] Preferably, in step S1, a sodium hydroxide solution with a concentration of 0.2-0.3 mol / L is used to adjust the pH value of the system to 10.5-11.

[0016] Preferably, in step S1, epichlorohydrin is added at a rate of 4-5% per minute based on the total weight of epichlorohydrin.

[0017] Preferably, in step S1, the temperature of the constant temperature water bath is 40-45° C., the stirring time of the constant temperature water bath is 4-6 h, and the stirring speed of the constant temperature water bath is 250-350 rpm.

[0018] Preferably, in step S1, the drying temperature is 60-65°C and the drying time is 18-22 hours.

[0019] Preferably, in step S2, the pretreated silk protein nanofibers and hydroxyapatite powder are mixed and stirred, the stirring time is 10-20 min, and the stirring speed is 200-300 rpm.

[0020] Preferably, in step S2, ball milling is performed by a planetary ball mill, the ball milling time is 8-9 hours, and the ball milling speed is 200-300 rpm.

[0021] Preferably, in step S2, the freeze-drying temperature is -45--50°C, and the freeze-drying time is 36-40 hours.

[0022] Preferably, in step S2, sintering is performed in a high-temperature sintering furnace, the sintering time is 2-3 hours, and the sintering temperature is 1000-1100°C.

[0023] Preferably, in step S3, the diatomaceous earth is calcined in a muffle furnace at a calcination temperature of 500-600° C. and a calcination time of 3-4 hours.

[0024] Preferably, in step S3, anhydrous ethanol and water are added and stirred for 0.5-1 h at a stirring speed of 350-450 rpm.

[0025] Preferably, in step S3, triethylamine is added at a rate of 1-2% per minute based on the total weight of the triethylamine.

[0026] Preferably, in step S3, the temperature of the constant temperature water bath is 23-27° C., the stirring time of the constant temperature water bath is 3-4 h, and the stirring speed of the constant temperature water bath is 200-300 rpm.

[0027] Preferably, in step S3, the drying temperature is 50-55° C. and the drying time is 20-24 h.

[0028] Preferably, in step S4, water, γ-aminopropyltriethoxysilane and polyethylene glycol are mixed and stirred for 20-30 min at a stirring speed of 200-300 rpm.

[0029] Preferably, in step S4, the pretreated diatomaceous earth is added and then stirred, the stirring time is 0.5-1 h, and the stirring speed is 300-400 rpm.

[0030] Preferably, in step S4, the ceramic substrate is immersed at a speed of 4-6 mm / min and the immersion time is 1-2 h.

[0031] Preferably, in step S4, the drying temperature is 58-62° C., and the drying time is 1.5-2 h.

[0032] Preferably, in step S4, curing is performed in a blast drying oven, and the curing time is 1-2 hours.

[0033] A ceramic diaphragm for separating waste lubricating oil is prepared by any of the above-mentioned methods for preparing a ceramic diaphragm for separating waste lubricating oil.

[0034] Beneficial effects:

[0035] In the present invention, silk protein nanofibers react with epichlorohydrin, graft specific groups, and then are compounded with hydroxyapatite powder by means of ball milling, sintering, etc. In this process, silk protein nanofibers interact with hydroxyapatite, and the special structure of the former is combined with the crystal structure of the latter, which optimizes the pore structure inside the ceramic substrate, reduces the irregularity and clogging risk of the pores, and reduces the flow resistance of waste lubricating oil when passing through, so that the membrane flux speed is in a reasonable range and can pass "uniformly and stably", improving the stability and repeatability of the waste lubricating oil separation process, and also developing the unique application value of silk protein nanofibers in the field of ceramic diaphragms for precise regulation of membrane flux.

[0036] In the present invention, diatomaceous earth is calcined and treated with triethylamine, and then mixed with polyethylene glycol and γ-aminopropyltriethoxysilane and coated on the surface of a ceramic substrate. Through operations such as impregnation, drying and curing, the diatomaceous earth and the ceramic substrate are tightly combined. On the basis of ensuring "uniform and stable", the "adaptive" membrane flux characteristics are further realized. When the working environment of the waste lubricating oil changes, such as when the impurity content increases, the porous structure and surface properties of the diatomaceous earth can respond according to these changes. Specifically, the interaction between diatomaceous earth, the substrate and polyethylene glycol will prompt the diaphragm to change the effective filtration area or surface charge properties of the pores, prevent impurities from clogging the pores, and maintain the "adaptive uniform and stable" membrane flux within a reasonable range.

[0037] In practical applications, the higher the membrane flux of a ceramic diaphragm, the better. Too high a membrane flux will lead to poor impurity interception, damage the microstructure of the diaphragm, and affect the stability of the entire separation system in practical applications. The present invention is different from the limitation of "blindly pursuing high flux" in traditional technologies that only rely on the inherent characteristics of a single material or a simple structure. It can make the ceramic diaphragm adapt to the treatment needs of waste lubricating oils of different qualities. In the case of large fluctuations in the composition of the waste lubricating oil, it can still maintain a good separation effect, reduce the decline in treatment effect caused by differences in lubricating oil quality, and do not need to frequently adjust the treatment process or replace the diaphragm, which reduces the equipment maintenance cost and replacement frequency, further improves the stability and reliability of the entire waste lubricating oil treatment system, and extends the service life of the equipment. DETAILED DESCRIPTION

[0038] The present invention will be further explained below in conjunction with specific embodiments.

[0039] Example 1

[0040] A method for preparing a ceramic diaphragm for separating waste lubricating oil comprises the following steps:

[0041] S1. Disperse 30 g of silk protein nanofibers in 350 g of water, stir for 20 min at a stirring speed of 250 rpm, adjust the pH value of the system to 10.5 with a sodium hydroxide solution having a concentration of 0.2 mol / L, add 12 g of epichlorohydrin, and add epichlorohydrin at a rate of 4% per minute based on the total weight of epichlorohydrin, stir in a constant temperature water bath at 40° C. for 4 h at a stirring speed of 250 rpm, filter, collect the precipitate, wash, and dry at 60° C. for 18 h to obtain pretreated silk protein nanofibers;

[0042] S2, mixing the pretreated silk protein nanofibers and 500g hydroxyapatite powder, stirring for 10min at a stirring speed of 200rpm, adding 400g water, 25g gelatin, and 3g sodium hexametaphosphate, ball milling for 8h with a planetary ball mill at a speed of 200rpm, pouring into a mold, freeze drying at -45°C for 36h, sintering in a high-temperature sintering furnace for 2h at a sintering temperature of 1000°C, cooling, and polishing the surface to obtain a ceramic substrate;

[0043] S3, 80g of diatomaceous earth was calcined at 500°C for 3h in a muffle furnace, cooled, 400g of anhydrous ethanol and 50g of water were added, stirred for 0.5h at a stirring speed of 350rpm, 15g of triethylamine was added, and the total weight of triethylamine was used as a basis, and the addition rate of triethylamine was 1% per minute, and the mixture was stirred in a constant temperature water bath at 23°C for 3h at a stirring speed of 200rpm, filtered, washed, and dried at 50°C for 20h to obtain pretreated diatomaceous earth;

[0044] S4. Mix 380g of water, 3g of γ-aminopropyltriethoxysilane and 20g of polyethylene glycol, stir for 20min at a stirring speed of 200rpm, add pretreated diatomaceous earth, stir for 0.5h at a stirring speed of 300rpm, immerse the ceramic substrate at an immersion speed of 4mm / min and an immersion time of 1h, dry at 58°C for 1.5h, and cure in a forced air drying oven for 1h to obtain a ceramic diaphragm for separation of waste lubricating oil.

[0045] Example 2

[0046] A method for preparing a ceramic diaphragm for separating waste lubricating oil comprises the following steps:

[0047] S1. Disperse 50 g of silk protein nanofibers in 400 g of water, stir for 30 min at a stirring speed of 350 rpm, adjust the pH value of the system to 11 with a sodium hydroxide solution with a concentration of 0.3 mol / L, add 16 g of epichlorohydrin, and add epichlorohydrin at a rate of 5% per minute based on the total weight of epichlorohydrin, stir in a constant temperature water bath at 45°C for 6 h at a stirring speed of 350 rpm, filter, collect the precipitate, wash, and dry at 65°C for 22 h to obtain pretreated silk protein nanofibers;

[0048] S2, mixing the pretreated silk protein nanofibers and 550g hydroxyapatite powder, stirring for 20min at a stirring speed of 300rpm, adding 500g water, 35g gelatin, and 5g sodium hexametaphosphate, ball milling for 9h with a planetary ball mill at a speed of 300rpm, pouring into a mold, freeze drying at -50°C for 40h, sintering in a high-temperature sintering furnace for 3h at a sintering temperature of 1100°C, cooling, and polishing the surface to obtain a ceramic substrate;

[0049] S3, calcining 100g of diatomaceous earth at 600°C for 4h in a muffle furnace, cooling, adding 500g of anhydrous ethanol and 80g of water, stirring for 1h, stirring at a speed of 450rpm, adding 30g of triethylamine, based on the total weight of triethylamine, the addition rate of triethylamine is 2% per minute, stirring in a constant temperature water bath at 27°C for 4h, stirring at a speed of 300rpm, filtering, washing, and drying at 55°C for 24h to obtain pretreated diatomaceous earth;

[0050] S4. Mix 400g of water, 5g of γ-aminopropyltriethoxysilane and 40g of polyethylene glycol, stir for 30min at a stirring speed of 300rpm, add pretreated diatomaceous earth, stir for 1h at a stirring speed of 400rpm, immerse the ceramic substrate at an immersion speed of 6mm / min and an immersion time of 2h, dry at 62°C for 2h, and cure in a forced air drying oven for 2h to obtain a ceramic diaphragm for separation of waste lubricating oil.

[0051] Example 3

[0052] A method for preparing a ceramic diaphragm for separating waste lubricating oil comprises the following steps:

[0053] S1. Disperse 35g of silk protein nanofibers in 360g of water, stir for 22min at a stirring speed of 270rpm, adjust the pH value of the system to 10.6 with a sodium hydroxide solution having a concentration of 0.22mol / L, add 13g of epichlorohydrin, and add epichlorohydrin at a rate of 4.2% per minute based on the total weight of epichlorohydrin, stir in a constant temperature water bath at 41°C for 4.5h at a stirring speed of 270rpm, filter, collect the precipitate, wash, and dry at 61°C for 19h to obtain pretreated silk protein nanofibers;

[0054] S2, pretreated silk protein nanofibers and 510g hydroxyapatite powder were mixed, stirred for 12min at a stirring speed of 220rpm, 420g water, 27g gelatin, and 3.5g sodium hexametaphosphate were added, ball milled by a planetary ball mill for 8.2h at a speed of 220rpm, poured into a mold, freeze-dried at -46°C for 37h, sintered in a high-temperature sintering furnace for 2.2h at a sintering temperature of 1020°C, cooled, and polished to obtain a ceramic substrate;

[0055] S3, 85g of diatomaceous earth was calcined at 520°C for 3.2h in a muffle furnace, cooled, 420g of anhydrous ethanol and 60g of water were added, stirred for 0.6h at a stirring speed of 370rpm, 18g of triethylamine was added, and the addition rate of triethylamine was 1.2% per minute based on the total weight of triethylamine, stirred in a constant temperature water bath at 24°C for 3.2h at a stirring speed of 220rpm, filtered, washed, and dried at 51°C for 21h to obtain pretreated diatomaceous earth;

[0056] S4. Mix 385g of water, 3.5g of γ-aminopropyltriethoxysilane and 25g of polyethylene glycol, stir for 22min at a stirring speed of 220rpm, add pretreated diatomaceous earth, stir for 0.6h at a stirring speed of 320rpm, immerse the ceramic substrate at an immersion speed of 4.5mm / min and an immersion time of 1.2h, dry at 59°C for 1.6h, and cure in a forced air drying oven for 1.2h to obtain a ceramic diaphragm for separation of waste lubricating oil.

[0057] Example 4

[0058] A method for preparing a ceramic diaphragm for separating waste lubricating oil comprises the following steps:

[0059] S1. Disperse 45g of silk protein nanofibers in 390g of water, stir for 28min at a stirring speed of 330rpm, adjust the pH value of the system to 10.9 with a sodium hydroxide solution having a concentration of 0.28mol / L, add 15g of epichlorohydrin, and add epichlorohydrin at a rate of 4.8% per minute based on the total weight of epichlorohydrin, stir in a constant temperature water bath at 44°C for 5.5h at a stirring speed of 330rpm, filter, collect the precipitate, wash, and dry at 64°C for 21h to obtain pretreated silk protein nanofibers;

[0060] S2, pretreated silk protein nanofibers and 540g hydroxyapatite powder were mixed, stirred for 18min at a stirring speed of 280rpm, 480g water, 32g gelatin, and 4.5g sodium hexametaphosphate were added, ball milled for 8.8h by a planetary ball mill at a speed of 280rpm, poured into a mold, freeze-dried at -49°C for 39h, sintered in a high-temperature sintering furnace for 2.8h at a sintering temperature of 1080°C, cooled, and polished to obtain a ceramic substrate;

[0061] S3, calcining 95g of diatomaceous earth at 580°C for 3.8h in a muffle furnace, cooling, adding 480g of anhydrous ethanol and 70g of water, stirring for 0.9h, stirring at a speed of 430rpm, adding 27g of triethylamine, based on the total weight of triethylamine, the addition rate of triethylamine is 1.8% per minute, stirring in a constant temperature water bath at 26°C for 3.8h, stirring at a speed of 280rpm, filtering, washing, and drying at 54°C for 23h to obtain pretreated diatomaceous earth;

[0062] S4. Mix 395g of water, 4.5g of γ-aminopropyltriethoxysilane and 35g of polyethylene glycol, stir for 28min at a stirring speed of 280rpm, add pretreated diatomaceous earth, stir for 0.9h at a stirring speed of 380rpm, immerse the ceramic substrate at an immersion speed of 5.5mm / min and an immersion time of 1.8h, dry at 61°C for 1.9h, and cure in a forced air drying oven for 1.8h to obtain a ceramic diaphragm for separation of waste lubricating oil.

[0063] Example 5

[0064] A method for preparing a ceramic diaphragm for separating waste lubricating oil comprises the following steps:

[0065] S1. Disperse 40 g of silk protein nanofibers in 370 g of water, stir for 25 min at a stirring speed of 300 rpm, adjust the pH value of the system to 10.7 with a sodium hydroxide solution having a concentration of 0.25 mol / L, add 14 g of epichlorohydrin, and add epichlorohydrin at a rate of 4.5% per minute based on the total weight of epichlorohydrin, stir in a constant temperature water bath at 42° C. for 5 h at a stirring speed of 300 rpm, filter, collect the precipitate, wash, and dry at 62° C. for 20 h to obtain pretreated silk protein nanofibers;

[0066] S2, pretreated silk protein nanofibers and 520g hydroxyapatite powder were mixed, stirred for 15min at a stirring speed of 250rpm, 450g water, 30g gelatin and 4g sodium hexametaphosphate were added, ball milled for 8.5h at a speed of 250rpm by a planetary ball mill, poured into a mold, freeze-dried at -47°C for 38h, sintered in a high-temperature sintering furnace for 2.5h at a sintering temperature of 1050°C, cooled, and polished to obtain a ceramic substrate;

[0067] S3, calcining 90g of diatomaceous earth at 550°C for 3.5h in a muffle furnace, cooling, adding 450g of anhydrous ethanol and 65g of water, stirring for 0.7h, stirring at a speed of 400rpm, adding 22g of triethylamine, based on the total weight of triethylamine, the addition rate of triethylamine is 1.5% per minute, stirring in a constant temperature water bath at 25°C for 3.5h, stirring at a speed of 250rpm, filtering, washing, and drying at 52°C for 22h to obtain pretreated diatomaceous earth;

[0068] S4. Mix 390g of water, 4g of γ-aminopropyltriethoxysilane and 30g of polyethylene glycol, stir for 25min at a stirring speed of 250rpm, add pretreated diatomaceous earth, stir for 0.7h at a stirring speed of 350rpm, immerse the ceramic substrate at an immersion speed of 5mm / min and an immersion time of 1.5h, dry at 60°C for 1.7h, and cure in a forced air drying oven for 1.5h to obtain a ceramic diaphragm for separation of waste lubricating oil.

[0069] Comparative Example 1

[0070] The difference between Comparative Example 1 and Example 5 is that: no "silk protein nanofiber" is added;

[0071] A method for preparing a ceramic diaphragm comprises the following steps:

[0072] S1. 520 g hydroxyapatite powder, 450 g water, 30 g gelatin and 4 g sodium hexametaphosphate were mixed, stirred for 15 min at a stirring speed of 250 rpm, ball milled for 8.5 h at a speed of 250 rpm in a planetary ball mill, poured into a mold, freeze-dried at -47 ° C for 38 h, sintered in a high-temperature sintering furnace for 2.5 h at a sintering temperature of 1050 ° C, cooled, and polished to obtain a ceramic substrate;

[0073] S2, 90g of diatomaceous earth was calcined at 550°C for 3.5h in a muffle furnace, cooled, 450g of anhydrous ethanol and 65g of water were added, stirred for 0.7h at a stirring speed of 400rpm, 22g of triethylamine was added, and the total weight of triethylamine was used as a basis, and the addition rate of triethylamine was 1.5% per minute, and the mixture was stirred in a constant temperature water bath at 25°C for 3.5h at a stirring speed of 250rpm, filtered, washed, and dried at 52°C for 22h to obtain pretreated diatomaceous earth;

[0074] S3. Mix 390g of water, 4g of γ-aminopropyltriethoxysilane and 30g of polyethylene glycol, stir for 25min at a stirring speed of 250rpm, add pretreated diatomaceous earth, stir for 0.7h at a stirring speed of 350rpm, immerse the ceramic substrate at an immersion speed of 5mm / min and an immersion time of 1.5h, dry at 60°C for 1.7h, and cure in a forced air drying oven for 1.5h to obtain a ceramic diaphragm.

[0075] Comparative Example 2

[0076] The difference between Comparative Example 2 and Example 5 is that the pretreated silk protein nanofibers in step S2 are replaced with silk protein nanofibers;

[0077] A method for preparing a ceramic diaphragm comprises the following steps:

[0078] S1. Mix 40 g of silk protein nanofibers and 520 g of hydroxyapatite powder, stir for 15 min at a stirring speed of 250 rpm, add 450 g of water, 30 g of gelatin, and 4 g of sodium hexametaphosphate, and mill for 8.5 h with a planetary ball mill at a speed of 250 rpm. Pour into a mold, freeze-dry at -47 ° C for 38 h, sinter in a high-temperature sintering furnace for 2.5 h at a sintering temperature of 1050 ° C, cool, and polish the surface to obtain a ceramic substrate;

[0079] S2, 90g of diatomaceous earth was calcined at 550°C for 3.5h in a muffle furnace, cooled, 450g of anhydrous ethanol and 65g of water were added, stirred for 0.7h at a stirring speed of 400rpm, 22g of triethylamine was added, and the total weight of triethylamine was used as a basis, and the addition rate of triethylamine was 1.5% per minute, and the mixture was stirred in a constant temperature water bath at 25°C for 3.5h at a stirring speed of 250rpm, filtered, washed, and dried at 52°C for 22h to obtain pretreated diatomaceous earth;

[0080] S3. Mix 390g of water, 4g of γ-aminopropyltriethoxysilane and 30g of polyethylene glycol, stir for 25min at a stirring speed of 250rpm, add pretreated diatomaceous earth, stir for 0.7h at a stirring speed of 350rpm, immerse the ceramic substrate at an immersion speed of 5mm / min and an immersion time of 1.5h, dry at 60°C for 1.7h, and cure in a forced air drying oven for 1.5h to obtain a ceramic diaphragm.

[0081] Comparative Example 3

[0082] The difference between Comparative Example 3 and Example 5 is that: no "diatomaceous earth" is added;

[0083] A method for preparing a ceramic diaphragm comprises the following steps:

[0084] S1. Disperse 40 g of silk protein nanofibers in 370 g of water, stir for 25 min at a stirring speed of 300 rpm, adjust the pH value of the system to 10.7 with a sodium hydroxide solution having a concentration of 0.25 mol / L, add 14 g of epichlorohydrin, and add epichlorohydrin at a rate of 4.5% per minute based on the total weight of epichlorohydrin, stir in a constant temperature water bath at 42° C. for 5 h at a stirring speed of 300 rpm, filter, collect the precipitate, wash, and dry at 62° C. for 20 h to obtain pretreated silk protein nanofibers;

[0085] S2, pretreated silk protein nanofibers and 520g hydroxyapatite powder were mixed, stirred for 15min at a stirring speed of 250rpm, 450g water, 30g gelatin and 4g sodium hexametaphosphate were added, ball milled for 8.5h at a speed of 250rpm by a planetary ball mill, poured into a mold, freeze-dried at -47°C for 38h, sintered in a high-temperature sintering furnace for 2.5h at a sintering temperature of 1050°C, cooled, and polished to obtain a ceramic substrate;

[0086] S3. Mix 390g of water, 4g of γ-aminopropyltriethoxysilane and 30g of polyethylene glycol, stir for 25min at a stirring speed of 250rpm, immerse the ceramic substrate at an immersion speed of 5mm / min and an immersion time of 1.5h, dry at 60°C for 1.7h, and cure in a forced air drying oven for 1.5h to obtain a ceramic diaphragm.

[0087] Comparative Example 4

[0088] The difference between Comparative Example 4 and Example 5 is that the pretreated diatomaceous earth in step S4 is replaced with diatomaceous earth;

[0089] A method for preparing a ceramic diaphragm comprises the following steps:

[0090] S1. Disperse 40 g of silk protein nanofibers in 370 g of water, stir for 25 min at a stirring speed of 300 rpm, adjust the pH value of the system to 10.7 with a sodium hydroxide solution having a concentration of 0.25 mol / L, add 14 g of epichlorohydrin, and add epichlorohydrin at a rate of 4.5% per minute based on the total weight of epichlorohydrin, stir in a constant temperature water bath at 42° C. for 5 h at a stirring speed of 300 rpm, filter, collect the precipitate, wash, and dry at 62° C. for 20 h to obtain pretreated silk protein nanofibers;

[0091] S2, pretreated silk protein nanofibers and 520g hydroxyapatite powder were mixed, stirred for 15min at a stirring speed of 250rpm, 450g water, 30g gelatin and 4g sodium hexametaphosphate were added, ball milled for 8.5h at a speed of 250rpm by a planetary ball mill, poured into a mold, freeze-dried at -47°C for 38h, sintered in a high-temperature sintering furnace for 2.5h at a sintering temperature of 1050°C, cooled, and polished to obtain a ceramic substrate;

[0092] S3. Mix 390g of water, 4g of γ-aminopropyltriethoxysilane and 30g of polyethylene glycol, stir for 25min at a stirring speed of 250rpm, add 90g of diatomaceous earth, stir for 0.7h at a stirring speed of 350rpm, immerse the ceramic substrate at an immersion speed of 5mm / min and an immersion time of 1.5h, dry at 60°C for 1.7h, and cure in a forced air drying oven for 1.5h to obtain a ceramic diaphragm.

[0093] Performance Testing

[0094] Membrane flux: The membrane flux of the ceramic diaphragms prepared in the above embodiments and comparative examples was tested according to GB / T 39717-2020. The results are shown in Table 1 below.

[0095] Flux standard deviation: The flux standard deviation of the ceramic diaphragms prepared in the above embodiments and comparative examples was tested according to GB / T 39717-2020. The results are shown in Table 1 below.

[0096] Flux change rate before and after the impurity content changes: Pour the waste lubricating oil with low impurity content and high impurity content into the liquid inlet container respectively; turn on the liquid inlet pump to allow the waste lubricating oil to pass through the ceramic diaphragm, and record the data after the liquid is stable. The results are shown in Table 1 below.

[0097] Calculation formula:

[0098] J is membrane flux;

[0099] V is the volume of waste lubricating oil passing through;

[0100] A is the effective filtration area of ​​the ceramic diaphragm;

[0101] t is time.

[0102] (2)

[0103] ΔJ is the flux change rate before and after the impurity content changes;

[0104] J1 is the waste lubricating oil flux with high impurity content;

[0105] J0 is the waste lubricating oil flux with low impurity content;

[0106] Table 1 Performance test results

[0107]

[0108] Data Analysis:

[0109] From the data of Examples 1-5 in Table 1, it can be seen that the ceramic diaphragm for waste lubricating oil separation prepared by the present invention has obvious advantages in the parameter results of "membrane flux", "flux standard deviation" and "flux change rate before and after impurity content changes". First, the membrane flux can reach 181.25 (L / (m 2 ·h)), the standard deviation of the flux can reach 2.85(L / (m 2 h), indicating that it maintains good uniform speed stability within the reasonable range of membrane flux. At the same time, the flux change rate before and after the impurity content changes can reach -5.16%, which shows that it can maintain good adaptability in the face of changes in impurity content, and can have obvious advantages in the actual application of waste lubricating oil separation. It can better adapt to the treatment needs of waste lubricating oil of different qualities, improve separation efficiency and stability, reduce equipment maintenance costs, extend the service life of the diaphragm, and promote the development of waste lubricating oil treatment technology.

[0110] From the data of Example 5 and Comparative Examples 1 and 2 in Table 1, it can be seen that the addition of silk protein nanofibers and their activation significantly improves the "uniform stability" performance of the membrane flux and enhances its "self-adaptive" ability. This is mainly because the silk protein nanofibers themselves have a large specific surface area, which can provide more action sites for the adsorption and separation of waste lubricating oil, and help to improve the separation efficiency. At the same time, the silk protein nanofibers have certain flexibility and strength, which can play a reinforcing role in the ceramic diaphragm, help to maintain the structural integrity when the diaphragm is subjected to external forces, avoid cracks or damage due to brittleness, and thus maintain stable filtration performance; then, continue to graft active groups on the silk protein nanofibers, and then in the process of composite with hydroxyapatite, further optimize the pore structure inside the ceramic substrate, reduce the irregularity of the pores and the risk of clogging, so that the flow resistance of the waste lubricating oil is reduced when passing through, and the membrane flux can be stabilized in a reasonable range and maintain a better uniform stability. When facing changes in impurity content, the diaphragm can also maintain good adaptability with a stable structure.

[0111] From the data of Example 5 and Comparative Examples 3 and 4 in Table 1, it can be seen that the addition and treatment of diatomite significantly improves the "uniform stability" performance of the membrane flux and enhances its "adaptive" ability. This is because diatomite itself has a rich microporous and mesoporous structure, which can be used as a channel for molecular screening. According to the size difference between impurity molecules and lubricating oil molecules, lubricating oil molecules are allowed to pass smoothly, while larger impurity molecules are intercepted to achieve the initial separation of waste lubricating oil. At the same time, diatomite has good chemical stability, which can ensure the stability of the entire diaphragm system; further, amino groups, alkyl groups and other groups are grafted on the surface of diatomite to optimize its surface properties, enhance its affinity with non-polar components in waste lubricating oil, improve separation selectivity, and help maintain the stability of membrane flux. At the same time, the reactive sites provided by the amino group enhance the binding force with the ceramic substrate and polyethylene glycol, optimize the structural integrity and stability of the diaphragm, keep the membrane flux within a reasonable range, and when the impurity content changes, the diaphragm changes the effective filtration area or surface charge properties of the pores through the response of its porous structure and surface properties, thereby maintaining the membrane flux relatively stable, reflecting good adaptability.

[0112] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for preparing a ceramic diaphragm for separating waste lubricating oil, characterized in that: The steps include: S1, dispersing silk protein nanofibers in water, stirring, adjusting the pH value of the system, adding epichlorohydrin, stirring in a constant temperature water bath, filtering, collecting precipitates, washing, and drying to obtain pretreated silk protein nanofibers; S2, mixing the pretreated silk protein nanofibers and hydroxyapatite powder, stirring, adding water, gelatin, and sodium hexametaphosphate, ball milling, pouring into a mold, freeze drying, sintering, cooling, and polishing the surface to obtain a ceramic substrate; S3, calcining the diatomaceous earth, cooling, adding anhydrous ethanol and water, stirring, adding triethylamine, stirring in a constant temperature water bath, filtering, washing, and drying to obtain pretreated diatomaceous earth; S4, mixing water, γ-aminopropyltriethoxysilane and polyethylene glycol, stirring, adding pretreated diatomaceous earth, stirring, immersing the ceramic substrate, drying, and curing to obtain a ceramic diaphragm for separating waste lubricating oil.

2. The method for preparing the ceramic diaphragm for separating waste lubricating oil according to claim 1, characterized in that: The weight ratio of silk protein nanofiber, epichlorohydrin, hydroxyapatite powder, gelatin, sodium hexametaphosphate, diatomaceous earth, anhydrous ethanol, triethylamine, γ-aminopropyltriethoxysilane and polyethylene glycol is 3-5:1.2-1.6:50-55:2.5-3.5:0.3-0.5:8-10:40-50:1.5-3:0.3-0.5:2-4.

3. The method for preparing the ceramic diaphragm for separating waste lubricating oil according to claim 1, characterized in that: In step S1, a sodium hydroxide solution with a concentration of 0.2-0.3 mol / L is used to adjust the pH value of the system to 10.5-11.

4. The method for preparing the ceramic diaphragm for separating waste lubricating oil according to claim 1, characterized in that: In step S1, epichlorohydrin is added at a rate of 4-5% per minute based on the total weight of epichlorohydrin.

5. The method for preparing the ceramic diaphragm for separating waste lubricating oil according to claim 1, characterized in that: In step S2, the freeze-drying temperature is -45--50°C, and the freeze-drying time is 36-40 hours.

6. The method for preparing the ceramic diaphragm for separating waste lubricating oil according to claim 1, characterized in that: In step S3, diatomaceous earth is calcined in a muffle furnace at a calcination temperature of 500-600° C. for 3-4 hours.

7. The method for preparing the ceramic diaphragm for separating waste lubricating oil according to claim 1, characterized in that: In step S3, triethylamine is added, and the addition rate of triethylamine is 1-2% per minute based on the total weight of triethylamine.

8. The method for preparing the ceramic diaphragm for separating waste lubricating oil according to claim 1, characterized in that: In step S4, the ceramic substrate is immersed at a speed of 4-6 mm / min and a time of 1-2 h.

9. The method for preparing the ceramic diaphragm for separating waste lubricating oil according to claim 1, characterized in that: In step S4, the material is cured in a blast drying oven for 1-2 hours.

10. A ceramic diaphragm for separating waste lubricating oil, characterized in that: The waste lubricating oil separation ceramic diaphragm is manufactured by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Silk composite film and preparation method thereof

    CN106543481A

  • Silk fibroin and polyurethane blending film preparation method

    CN106543744A

  • Anti-pollution ceramic membrane for separating waste lubricant oil and preparation method

    CN107335340A

  • High-adhesion coating and preparation method thereof

    CN119171009A

  • Method for manufacturing porous clay-based ceramic membrane with ceramic coating layer and ceramic membrane manufactured thereby

    KR1020150092518A

Cited By

  • Bionic mineralized silkworm cocoon-based filter membrane and preparation method thereof

    CN121082127A